UKURAN LINGKAR LENGAN ATAS DENGAN BERAT BADAN BAYI LAHIR DI BPS. ANA SUSANTI BALONGBENDO 2010 - Ishaq, Latifatul; Yuliani, Farida (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2012)
Women with chronic conditions of less energy or less nutritional status during pregnancy often give birth to LBW. The purpose of this study was to determine the relationship LILA size of pregnant women with weight babies born in BPS Ana Susanti. AMD. Keb, Balongbendo, Sidoarjo. The study used a retrospective design and the population is used throughout the birthing mother in 2010 as many as 138 people with a sample of 102 people that selected using Simple Random Sampling. The results analyzed using the test statistic wilxocon. Result showed the largest percentage (78.4%) of the group of respondents that have a size of ? 23.5 cm Lila there are 80 respondents. And the largest percentage of babies born to have a normal body weight that is there were 66 infants (64.7%). There is a significant relationship between the size of LILA pregnant women with weight babies born.LILA have relationships of pregnant women with birth weight performed the Wilcoxon test with significant level of 0.05 obtained value of Z = (3.494) with a significant level of 0.000. Due to a significant level of 0.000 then Ho is rejected, it means there is a relationship pregnant with Lila size birth weight. This is because of the intake of adequate nutrition at the time before and during pregnancy. Thus the required monitoring of health and nutritional status of pregnant mothers either in early pregnancy and during pregnancy is an effort to approach a potential in relation to increased maternal and child welfare.Key words: Lila, weight newborns